Pemahaman Materi Pelajaran Selama Belajar dari Rumah Pada Remaja Jorong Tampat Kanagarian Padang Laweh Kecamatan Sungai Pua Kabupaten Agam - Hajar, Sabatul (Kognitif: Jurnal Pendidikan dan Inovasi Pembelajaran, 2025)
This study was motivated by a phenomenon observed by the author in the field, namely that in Jorong Tampat Kanagarian Padang Laweh, Sungai Pua District, Agam Regency, there were teenagers conducting BDR (learning at home) teaching and learning activities, whereby learning that normally took place in classrooms according to a specific schedule was changed to learning in their own rooms at times that were not practical according to the learning schedule, thus creating operational restrictions on education, referred to as “online learning.” Teachers provide structured lesson materials and assignments to adolescents using social media groups. This study aims to describe the understanding of lesson materials during home-based learning among adolescents in Jorong Tampat Kanagarian Padang Laweh, Sungai Puar District, Agam Regency. This study uses a descriptive qualitative approach with 3 key informants (adolescents) and 3 supporting informants (parents) in Jorong Tampat Kanagarin Padang Laweh. In collecting data, the researcher used interview and observation methods. The data analysis techniques used were data reduction, data display, and data verification. To test the validity of the data, we compared what people said about the research situation with what they said throughout the research period. Based on the results of the study, it can be concluded that teenagers have difficulty understanding the subject matter while studying from home, because the current learning process is conducted remotely. Meanwhile, teenagers quickly understand the subject matter through lectures by teachers. However, teenagers can overcome this by using the internet to support smooth learning from home, so that they can complete the assignments given by teachers on time. However, teenagers rely too much on the internet. Teenagers lack enthusiasm for learning from home, only understanding the subject matter when there are assignments and using little time, because they cannot allocate time for studying at home. Understanding the subject matter while learning from home requires the attention of every parent towards their child.